Chronic sustained hypoxia-induced redox remodeling causes contractile dysfunction in mouse sternohyoid muscle - Lewis, Philip; Sheehan, David; Soares, Renata; Varela Coelho, Ana; O'Halloran, Ken D. (Frontiers in Physiology, 2015)
Chronic sustained hypoxia (CH) induces structural and functional adaptations in respiratory muscles of animal models, however the underlying molecular mechanisms are unclear. This study explores the putative role of CH-induced redox remodeling in a translational mouse model, with a focus on the sternohyoid - a representative upper airway dilator muscle involved in the control of pharyngeal airway caliber. We hypothesized that exposure to CH induces redox disturbance in mouse sternohyoid muscle in a time-dependent manner affecting metabolic capacity and contractile performance. C57Bl6/J mice were exposed to normoxia or normobaric CH (FiO2=0.1) for one, three, or six weeks. A second cohort of animals was exposed to CH for six weeks with and without antioxidant supplementation (tempol or N-acetyl cysteine in the drinking water). Following CH exposure, we performed 2D redox proteomics with mass spectrometry, metabolic enzyme activity assays, and cell-signalling assays. Additionally, we assessed isotonic contractile and endurance properties ex vivo. Temporal changes in protein oxidation and glycolytic enzyme activities were observed. Redox modulation of sternohyoid muscle proteins key to contraction, metabolism and cellular homeostasis was identified. There was no change in redox-sensitive proteasome activity or HIF-1α content, but CH decreased phospho-JNK content independent of antioxidant supplementation. CH was detrimental to sternohyoid force- and power-generating capacity and this was prevented by chronic antioxidant supplementation. We conclude that CH causes upper airway dilator muscle dysfunction due to redox modulation of proteins key to function and homeostasis. Such changes could serve to further disrupt respiratory homeostasis in diseases characterized by CH such as chronic obstructive pulmonary disease. Antioxidants may have potential use as an adjunctive therapy in hypoxic respiratory disease.